Overview of the Use of Quantitative Methods in Research on Relationship Marketing with Alumni - Borges, Glauco José Ribeiro (2020)
The study maps an overview of the quantitative methods used in research on relationship marketing with alumni. It is a bibliographic study, with bibliometric analysis, which analyzed a bibliographic portfolio of 20 papers published until 2018 on the subject. The results show that most publications on the subject use structural equation modeling, confirmatory factor analysis and descriptive statistics. Cronbach's alpha is the most used scale reliability analysis. The two variables most analyzed in studies on the subject are university image and satisfaction, terms supported by the literature in the area. The study contributed to broaden the understanding about the use of quantitative methods in research on the subject and to point out some directions that may help in future studies.